STRATEGI PROGRAM ECO-PESANTREN DALAM MENGHADIRKAN KARAKTER PEDULI LINGKUNGAN TERHADAP PONDOK PESANTREN MALAHAYATI BANDAR LAMPUNG - Fifi Risana; Hamidah; Muhammad Adib; Azet Sampurna; A.Ikhlas Muhtar Hadi; Ali Murtadho; Baharudin; Ikhsan Mustofa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article discusses the strategies implemented by the Malahayati Islamic Boarding School in Bandar Lampung in forming environmentally conscious characters through the eco-boarding school program. As an Islamic-based educational institution, the Malahayati Islamic Boarding School in Bandar Lampung has an important role in instilling Islamic values ​​that also include aspects of caring for nature. The eco-boarding school program implemented in this boarding school aims to integrate character education with environmental conservation values. This study uses a qualitative method with an observation approach and in-depth interviews conducted with the Mudir (boarding school leader) and educators at the boarding school. Data obtained from interviews and documentation were analyzed using descriptive analysis techniques. The results of the study indicate that the eco-boarding school program implemented in the Malahayati Islamic Boarding School in Bandar Lampung has proven effective in increasing students' awareness and concern for the environment. Some of the main activities in this program include planting gardens, inter-class cleanliness competitions, and maintaining aquariums in students' rooms, which directly involve students in maintaining the cleanliness and sustainability of nature. This program also plays an important role in forming the character of students who are disciplined, responsible, and have a high sense of concern for the environment around them. It is expected that the implementation of this eco-pesantren program can be adopted by other Islamic boarding schools as an educational model that combines religious aspects with environmental preservation